THE ROLE OF ZISWAF INSTITUTIONS IN INCREASING THE ECONOMIC INDEPENDENCE OF VULNERABLE COMMUNITIES - Mabruroh, Ahda Inayati; Itang; Sulaeman Jajuli (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This study aims to explore in depth the role of productive economic empowerment strategies carried out by ZISWAF institutions. The research method used is a literature study with a qualitative approach, which focuses on literature search, analysis of various previous research results, and conceptual interpretation of the role of ZISWAF in community economic development. The results of the study show that ZISWAF institutions not only function as distributors of social funds to mustahik groups, but also play a strategic role as agents of economic transformation. This can be seen from the programs they run, including productive zakat management, skills training, small business assistance, and community development based on Islamic values. Through these programs, ZISWAF does not merely provide short-term assistance, but also builds the economic foundation of the community to be more independent and competitive. Furthermore, the empowerment strategy implemented by ZISWAF institutions has advantages in terms of sustainability. This is because the programs emphasize the economic independence of mustahik, so that they not only receive assistance but are also encouraged to become muzaki in the future.